HUBUNGAN ANTARA DUKUNGAN KELUARGA DENGAN ACTIVITY DAILY LIVING (ADL) PASIEN PASCA STROKE DI POLIKLINIK NEUROLOGI MAYAPADA HOSPITAL TANGERANG - Retno Andriati; Ayu Rahayu; Marsondang Situmeang; Dyna Meilolita Sirait; Netti Rodearni Damanik; Yanti Sakty Maria; Yulianingsih, Yulianingsih; Roma Tao Toba Muara Ria; Mara Imbang Satriawan Hasiolon; Perawat OPD 1 (Nusantara Hasana Journal, 2025)
Stroke is a cerebral vascular disease in which there is a failure of oxygen supply to brain cells so that they are most susceptible to damage and cause death. The purpose of this study was to determine whether there is a relationship between family support and activity daily living (ADL) in post-stroke patients in the neurology clinic of Mayapada Hospital Tangerang. This study used a correlation design with a cross-sectional research approach with data collection methods using a questionnaire. The results of the study showed that the age distribution of patients was half of the early elderly, namely 56% (17), the patient's gender was mostly male 63% (19), the patient's education was mostly high school education, namely 50% (15), the patient's work was half private employees, namely 50% (15), the patient's family support was mostly good 53% (16), the patient's Activity Daily Living (ADL) was mostly independent, namely 57% (17) and the results of the Chi-Square test obtained a Pvalue = 0.000 (Pvalue ≤ α = 0.05) with OR: 7.259-1115.914, it can be concluded that there is a relationship between family support and the independence of post-stroke patients in activity daily living (ADL) in the neurology clinic of Mayapada Tangerang Hospital.